Scalable Fabrication of Large-Scale Electrochromic Smart Windows for Superior Solar Radiation Regulation and Energy Savings - Tang, Yanbang; Yuan, Junyu; Zheng, Rongzong; Jia, Chunyang (Nano-Micro Letters, 2026)
Electrochromic smart windows (ESWs) can significantly reduce building energy consumption, but the high cost hinders large-scale production. The in situ growth of tungsten oxide (WO3) films is only by a simple immersion process, the silver nanowires (AgNWs) undergo oxidation to Ag+ ions through electron loss, and the liberated electrons provide driving force for the deposition of WO42−. Enabled the fabrication of large-area WO3 films and ESWs were fabricated under minimal laboratory conditions, demonstrating the economic feasibility, efficient and reliable nature of industrial production. Structural characterization and density functional theory calculations were combined to confirm that AgNWs effectively regulate oxygen vacancies of WO3 films and promote the in situ growth process. The optimized WO3 exhibits a maximum transmittance modulation of 90.8% and excellent cycling stability of 20,000 cycles. The large-scale WO3-based ESWs can save building energy up to 140.0 MJ m−2 compared to traditional windows in tropical regions, as verified by simulations more than 40 global cities. This research provides a new approach for improving the performance and industrial production of ESW, providing the full understanding and development direction to short the distance of the ESW commercial production. Highlights: 1 Propose the in-situ growth strategy of WO3 films and deeply explore the growth mechanism and reveal the "one stone, three birds" synergistic mechanism of silver nanowires. 2 The WO3-based electrochromic devices not only can achieve large-area fabrication, dual-band regulation, and excellent cycling stability, but also possess excellent photothermal control capabilities. 3 A uniform and large-scale WO3-based electrochromic smart windows of 6000 cm2 was fabricated through a simple device, which can save building energy up to 140.0 MJ m-2 compared to traditional windows.